2011
DOI: 10.17796/jcpd.36.2.f1m4283501374t22
|View full text |Cite
|
Sign up to set email alerts
|

Candida, Mutans Streptococci, Oral Hygiene and Caries in Children

Abstract: Objective: to test the association between Candida and mutans streptococci (ms), oral hygiene and caries levels and in children. Methods: 22 boys and 12 girls (age 6 to 14.5 years) participated in the study. Each participant received a toothbrush, and was asked to brush his/her teeth after proper instructions. Dental caries and oral hygiene were recorded. Candida and ms levels were determined in saliva samples. Results: Candida colonies were observed in 70.5% of the children. No association was found between C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 2 publications
0
8
1
1
Order By: Relevance
“…A study following 183 children over 7 years showed that early colonization with Candida was associated with caries onset in primary molars, but not in permanent first molars . In some other studies, however, association between caries and Candida was not supported .…”
Section: Microorganisms In Saliva As Biomarkers Of Cariesmentioning
confidence: 97%
“…A study following 183 children over 7 years showed that early colonization with Candida was associated with caries onset in primary molars, but not in permanent first molars . In some other studies, however, association between caries and Candida was not supported .…”
Section: Microorganisms In Saliva As Biomarkers Of Cariesmentioning
confidence: 97%
“…Evidence of the role that C. albicans plays in caries has been contradictory. Some studies have observed no significant differences between caries status (caries free or caries active) and C. albicans prevalence (20,21), while another showed there was no correlation between caries risk and C. albicans presence (22). In contrast, a study using a rodent caries model found that C. albicans had the ability to cause caries when fed a high-sucrose and -glucose diet (23).…”
mentioning
confidence: 99%
“…This is in correlation with the previous studies by Hossain et al [24], de Carvalho [20], Tony Jose [25], Ann Thomas [26], Fragkou et al [5], and others. However in the studies by Maijala et al [27], Peretz et al [28], and Ratson et al [29], no significant association between Candida and dental caries was found. This could be attributed to factors like difference in saliva rate, composition, buffering capacity etc.…”
Section: Comparison Of Zone Of Inhibition Between Ketoconazole and Prmentioning
confidence: 92%